Theoretical considerations for muscle-energy savings during distance running - Fletcher, J. R.; MacIntosh, B. R. (Journal of Biomechanics, 2018)
We have recently demonstrated that the triceps surae muscles energy cost (ECTS) represents a substantial portion of the total metabolic cost of running (Erun). Therefore, it seems relevant to evaluate the factors which dictate ECTS, namely the amount and velocity of shortening, since it is likely these factors will dictate Erun. Erun and triceps surae morphological and AT mechanical properties were obtained in 46 trained and elite male and female distance runners using ultrasonography and dynamometry. ECTS (J·stride-1) at the speed of lactate threshold (sLT) was estimated from AT force and crossbridge mechanics and energetics. To estimate the relative impact of these factors on ECTS, mean values for running speed, body mass, resting fascicle length (Lf), Achilles tendon stiffness and moment arm and maximum isometric plantarflexion torque were obtained. ECTS was calculated across a range (mean ± 1 sd) of values for each independent factor. Average sLT was 233 m·min-1. At this speed, ECTS was 255?J·stride-1. Estimated fascicle shortening velocity was 0.08 Vmax and the level of muscle activation was 84.7% of maximum isometric torque. Compared to the ECTS calculated from the lowest range of values obtained for each independent factor, higher AT stiffness was associated with a 39% reduction in ECTS, 81% reduction in fascicle shortening velocity and a 31% reduction in muscle activation. Longer AT moment arms and elevated body masses were associated with an increase in ECTS of 18% and 23%, respectively. These results demonstrate that a low ECTS is achieved primarily from a high AT stiffness and low body mass, which is exemplified in elite distance runners.